2006
DOI: 10.1074/jbc.m513281200
|View full text |Cite
|
Sign up to set email alerts
|

Transportin Is a Major Nuclear Import Receptor for c-Fos

Abstract: c-Fos, a component of the transcription factor AP-1, is rapidly imported into the nucleus after translation. We established an in vitro system using digitonin-permeabilized cells to analyze nuclear import of c-Fos in detail. Two import receptors of the importin ␤ superfamily, importin ␤ itself and transportin, promote import of c-Fos in vitro. Under conditions where importin ␤-dependent transport was blocked, c-Fos still accumulated in the nucleus in the presence of cytosol. Inhibition of the transportin-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 52 publications
3
49
0
Order By: Relevance
“…The fact that CD44 binds several proteins from the importin family, but that only one of them is sufficient for nuclear translocation is not surprising. It has been shown that the transcription factor c-Fos binds several importins, including importin ␤ and transportin1 (27). Detailed analysis showed that transportin1 plays the key role in the import of c-Fos.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that CD44 binds several proteins from the importin family, but that only one of them is sufficient for nuclear translocation is not surprising. It has been shown that the transcription factor c-Fos binds several importins, including importin ␤ and transportin1 (27). Detailed analysis showed that transportin1 plays the key role in the import of c-Fos.…”
Section: Discussionmentioning
confidence: 99%
“…The canonical Trn1 import signal (M9) was initially described for hnRNP A1, and analogous domains have been described for several other proteins that associate with Trn1/2 (3,22,26,31,37,41,43,54,67,68,(72)(73)(74)76). hnRNP F was previously shown to interact with and be imported by Trn1 (43,73), and hnRNP H was shown to interact with Trn1/2 (31).…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that the nuclear import of protein pVII could be reconstituted in digitonin-permeabilized cells by using either cytosol or the receptors that bound to pVII in vitro. The apparent promiscuity of protein pVII in exploiting several nuclear import pathways has been observed for several other transport cargoes (3,14,21,37). Some of these cargoes are highly basic and are capable of nucleic acid binding and, like pVII, appear to use the same NLS region for more than one import receptor (21,37).…”
mentioning
confidence: 99%